The Role of Langgar in Kampung Kauman Yogyakarta in Two Centuries of Village Development - Yetti, Aprodita Emma; Purwanto, Edi; Pandelaki, Edward Endrianto; Riskiyanto, Resza (Sinektika: Jurnal Arsitektur, 2025)
This article analyzes the role of langgar in Kampung Kauman Yogyakarta during the period of village development from 1773 to 1930. The three periods are when Kampung Kauman Yogyakarta first appeared, the second is during the batik industry period, and the third is during the birth of community organizations in Kampung Kauman Yogyakarta, namely Muhammadiyah and Aisyiyah. Langgar is a space for religious and social activities in Muslim-populated villages in Java, Indonesia. This study aims to explain the role of the seven langgars that still exist today in the socio-cultural life of Kampung Kauman Yogyakarta, related to local values, public space, and social roles. This research uses a qualitative method with the Grounded Theory method. This research explains that langgar in Kampung Kauman Yogyakarta is not only present as a place of worship but also as a role of a node for the development of village settlements and community social spaces. The output of this article is expected to be the basis for a research framework that needs to be developed to study the role of the langgar and the sustainability of settlements in Kampung Kauman Yogyakarta.